Analisis Pengaruh Keamanan, Kesehatan dan Keselamatan Kerja terhadap Kinerja Pegawai Kantor Penanggulangan Bencana Kabupaten Majene - Safriansyah, -; Naim, Muh. Rezky (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2019)
This research was conducted to improve ability quality security, occupational health and safety against the performance of an employe at the Office (OPD) disaster relief District of West Sulawesi Province of Majene. The purpose of this research was aimed to: analyse the influence of job security against the performance of an employe at the Office (OPD) Counter measure Bencana Regency of West Sulawesi Province of Majene, analyzing the influence of Safety against the performance of employees on Office (OPD) Counter measure Bencana Regency of West Sulawesi Province of Majene and outlines the influence of Safety against the performance of an employee at the Office (OPD) disaster relief District of West Sulawesi Province of Majene, as well as analyze that most independent variables which are the dominant influence on the dependent variables. The data used are the primary and secondary data. The population of the research was the entire corporate staff in Office Penanggulangan (OPD) Disaster Countries Majene West Sulawesi Province. The research is as many as 30 employees with sampling techniques. Data collection was done through kusioner, and documentation. Methods of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS program 24.00. The results showed in simultaan (together) shows the difference job security of 30.0%, occupational health of 43% compared with 88.5% Safety or on top of 0.05 is proving the influential third on performance Clerk at the Office of District disaster management (OPD) Majene West Sulawesi province. This indicates there is influence together job security, occupational health and safety against the performance of the Employee so that the purpose of this research through analysis, description and a description of the three variables can influence can match with the results of the analysis particularly in the Office of the District disaster management (OPD) Majene West Sulawesi province